2007
DOI: 10.1093/ps/86.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes as Feed Additive to Aid in Responses Against Eimeria Species in Coccidia-Vaccinated Broilers Fed Corn-Soybean Meal Diets with Different Protein Levels

Abstract: This research aimed to evaluate the effects of adding a combination of exogenous enzymes to starter diets varying in protein content and fed to broilers vaccinated at day of hatch with live oocysts and then challenged with mixed Eimeria spp. Five hundred four 1-d-old male Cobb-500 chickens were distributed in 72 cages. The design consisted of 12 treatments. Three anticoccidial control programs [ionophore (IO), coccidian vaccine (COV), and coccidia-vaccine + enzymes (COV + EC)] were evaluated under 3 CP levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…In a more severe challenge, Parker et al. ( 2007 ) reported reductions in average FI and WG of all treatments infected with mixed Eimeria spp. by 21 and 45%, respectively, whereas the FCR was increased by 43% compared with the average of the unchallenged control.…”
Section: Discussionmentioning
confidence: 99%
“…In a more severe challenge, Parker et al. ( 2007 ) reported reductions in average FI and WG of all treatments infected with mixed Eimeria spp. by 21 and 45%, respectively, whereas the FCR was increased by 43% compared with the average of the unchallenged control.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with a protease reduced negative impact of a coccidiosis infection (E. acervulina, E. maxima, and E. tenella) on body weight gain in broilers but had no effects on lesions and oocyst shedding (98). In contrast, Parker et al (99) showed that an enzyme blend (amylase, protease, and xylanase) fed to coccidiosis vaccinated broiler chicks had no effect on ileal nutrient digestibility or growth performance but reduced lesion scores. E. acervulina and E. maxima associated intestinal damage have been linked with adverse effects on bone health mainly because they infect duodenum and upper jejunum, the major sites of minerals absorption (85,100,101).…”
Section: Utility Of Feed Enzymes In Modulating Coccidiosis In Broilersmentioning
confidence: 99%
“…Feed enzymes can modulate GIT ecology reducing undigested nutrients and production of oligosaccharides with potential prebiotic effects (Figure 2) (24). For example, enzyme blend (amylase, protease, and xylanase) supplementation supported gut ecology that reduced intestinal lesion scores particularly in the ceca linked to altered microbial profiles in coccidia-vaccinated broilers (99). The authors interpreted that, although the enzyme blend did not influence ileal digestibility of nutrients it altered the characteristics of digesta such that ceca microbiota communities were altered.…”
Section: Utility Of Feed Enzymes In Modulating Coccidiosis In Broilersmentioning
confidence: 99%
“…Thus, identifying the suitable FA and nutrient supply which influences beneficial microbial community is essential (Hume et al, 2006; Parker et al, 2007). Denaturing gradient gel electrophoresis-polymerase chain reaction (DGGE-PCR) technique is one of DNA fingerprinting techniques which can be used to describe the microbial diversity of a variety of ecosystems in intestinal microbiota (Muyzer et al, 1993; Felske et al, 1998; Muyzer and Smalla, 1998; Konstantinov et al, 2003; Zhu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%